An interactive programming learning environment supporting paper computing and immediate evaluation for making thinking visible and traceable - Zhuang, YungYu; Lin, Yu-Hsuan; Liyanawatta, Mahesh; Saputro, Andito Haryo; Utami, Yuniati Dwi; Wang, Jen-Hang (Interactive learning environments, 2024)
Computer programming is essential nowadays but still challenging to learn due to its invisible thinking. Current programming environments are mostly designed for operating on computers directly to learn concrete programming, but this approach lacks the support for clarifying learners' thinking processes. On the other hand, using paper and pens shows usability in developing creative thinking, but it cannot help verify learners' thinking results due to its nature. To benefit from both paper and computers, we developed an interactive programming learning environment consisting of a paper board game, a computer system, and a digitalization mechanism. Learners can use the learning environment to draw down their thinking results and verify them by comparing them with the evaluation on the computer system immediately. Two experiments were conducted to compare this learning environment with paper board games and computer programming environments, respectively. The experimental results show that the subjects who learn in our environment can learn to program better than those who learn with the other two. The proposed environment is easy to prepare for learners in a classroom as their first step to programming learning. It can help learners cross over from paper board games for computational thinking to computer programming environments.